Theodore Burt Sayre correspondence - Sayre, Theodore Burt.
ALS written by Sayre while in the employ of theatrical producer Charles Frohman to Thomas F. Glancy regarding Glancy's dramatization of a work by Gilbert Parker.
Author. Born 1874.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Frohman, Charles, -- 1860-1915.; Glancy, Thomas F. -- Correspondence; Parker, Gilbert, -- 1862-1932.; Playwriting; Theater -- Production and direction